Analisis Kepatuhan Pekerja dalam Menggunakan Masker Respirator terhadap Paparan Uap Benzena di Area Filling Shed PT Pertamina Patra Niaga Fuel Terminal Meulaboh - Muhammad Arif; Jun Musnadi Is; Rubi Rimonda; Kiswanto Kiswanto; Perry Boy Chandra Siahaan (Universitas Pahlawan Tuanku Tambusai, 2026)
Exposure to benzene vapors in the downstream oil and gas industry poses a latent carcinogenic risk that threatens workers' respiratory health and hematopoietic systems. Personal Protective Equipment (PPE), including respirator masks, is the last resort in protecting workers from workplace hazards. This study aims to analyze in-depth the dynamics of worker compliance in the use of respirator masks and identify factors that influence their resistance to use in the filling shed area of ​​PT Pertamina Patra Niaga Fuel Terminal Meulaboh. The method used is descriptive qualitative with a purposive sampling approach. Data were collected through in-depth interviews with five informants (three operational workers, one HSE officer, and one supervisor) and participant observation using 20 field items. The results of the study indicate the occurrence of a phenomenon of pseudo-compliance (surface compliance), where workers only wear respirators during formal supervision. Based on the PRECEDE-PROCEED model, this non-compliance is triggered by a multidimensional accumulation: ergonomic barriers and environmental thermal constraints (enabling factors) in the form of tightness, stuffiness, and trapped sweat; cognitive devaluation and risk perception bias due to the asymptomatic nature of benzene (predisposing factors); and the blunting of organizational control functions (reinforcing factors) due to the absence of written administrative sanctions that provide a deterrent effect. This study concludes that safety interventions cannot be carried out partially, but must integrate engineering .techniques on the aspect of respirator comfort, ongoing behavioral education, and strict enforcement of internal regulations.